1990
DOI: 10.1007/bf01409476
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of carvedilol in man after intravenous and oral administration of the racemic compound

Abstract: The racemic compound carvedilol is a multiple-action oral antihypertensive drug that exhibits both vasodilator and non-selective beta-adrenergic blocking activities. The effects of the levorotatory S-enantiomer [S(-)-CARV] are vasodilatation and beta-blockade. The R(+)-enantiomer [R(+)-CARV] is a pure vasodilating agent. Quantitative determination of the enantiomers in human plasma by HPLC was carried out after formation of diastereoisomers with the chiral reagent 2,3,4,6-tetra-O-acetyl-beta-D-glucopyranosyl i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
0
18

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 8 publications
5
78
0
18
Order By: Relevance
“…45 Whereas b1-antagonism is primarily conferred by the S-enantiomer of carvedilol, the R-isoform is responsible for a1-blockade.…”
Section: B-blockersmentioning
confidence: 99%
“…45 Whereas b1-antagonism is primarily conferred by the S-enantiomer of carvedilol, the R-isoform is responsible for a1-blockade.…”
Section: B-blockersmentioning
confidence: 99%
“…Its solubility values are 51 mg mL À1 above pH 9.0, 23 mg mL À1 at pH 7 and about 100 mg mL À1 at pH 5 at room temperature [19]. Carvedilol undergoes significant stereoselective first-pass metabolism, resulting in low absolute bioavailability (30% or less) [20][21][22]. However, some sources suggest that this low bioavailability is the result of poor aqueous solubility [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…9) Absolute bioavailability upon oral administration is 31.1% and 15.1% for the R-and Senantiomers, respectively, and the difference in metabolic stability is attributed mainly to CYP2D6. 10,11) Carvedilol shows high plasma protein binding (98-99%), 12) and is known to bind to a 1 -acid glycoprotein with high affinity. 13) The COMMET study reported that serious adverse and CHF-related events in patients switching from metoprolol (a b 1 -selective agent) to carvedilol (a nonselective agent) were lower than in patients switching from carvedilol to metoprolol.…”
mentioning
confidence: 99%